2020
DOI: 10.31661/gmj.v9i0.1798
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality Incidence in Patients with Chronic Kidney Disease Based on Influential Prognostic Factors with Competing Risks Approach

Abstract: Background: Chronic Kidney Disease (CKD) is a disease in which the kidney’s functionality declines gradually. The aim of this study was to identify significant laboratory prognostic factors on death due to CKD in a clinical complex. Materials and Methods: A retrospective study including 109 patients with the end-stage renal disease treated at Iran Helal pharmaceutical and the clinical complex was conducted between 2014-2018. The survival time was set as the time interval between starting dialysis until death d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This might be due to concurrent low levels of iPTH or unobserved C-reactive protein. Saeedi et al also reported no signi cant impact of high albumin levels on HD patients' survival in a study utilizing a complex competing risks model (14).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This might be due to concurrent low levels of iPTH or unobserved C-reactive protein. Saeedi et al also reported no signi cant impact of high albumin levels on HD patients' survival in a study utilizing a complex competing risks model (14).…”
Section: Discussionmentioning
confidence: 96%
“…The results demonstrated that the male gender was associated with a higher risk of mortality. Similarly, Carrero et al concluded that, despite females having a greater prevalence of CKD, male HD patients had a higher mortality rate (14). Cardiovascular events are one of the most important causes of death in HD patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation